2009
DOI: 10.1055/s-0028-1112208
|View full text |Cite
|
Sign up to set email alerts
|

In vitroAnti-Influenza Viral Activities of Constituents fromCaesalpinia sappan

Abstract: Six constituents with neuraminidase (NA) inhibitory activity, namely brazilein, brazilin, protosappanin A, 3-deoxysappanchalcone, sappanchalcone and rhamnetin, were isolated from the hearthwood of Caesalpinia sappan (Leguminosae). Their in vitro anti-influenza virus activities were evaluated with the cytopathic effect (CPE) reduction method. The results showed that 3-deoxysappanchalcone and sappanchalcone exhibited the highest activity against influenza virus (H3N2) with IC50 values of 1.06 and 2.06 microg/mL,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 3 publications
1
60
0
Order By: Relevance
“…Brazilin (in SFN) has been reported to have many biological activities, including immune regulation, 19,20 blood vessel dilatation, 3,11,14 anticoagulation, 8,17 hypoglycemic effect, 10,13,15,16,26,27 oxidative damage inhibition, 6,28 antibiosis, 9 and anti-inflammatory effects. 4,5,7 In addition, it was demonstrated that brazilin powerfully broke deoxynucleic acid chains in anticancer screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brazilin (in SFN) has been reported to have many biological activities, including immune regulation, 19,20 blood vessel dilatation, 3,11,14 anticoagulation, 8,17 hypoglycemic effect, 10,13,15,16,26,27 oxidative damage inhibition, 6,28 antibiosis, 9 and anti-inflammatory effects. 4,5,7 In addition, it was demonstrated that brazilin powerfully broke deoxynucleic acid chains in anticancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…Brazilin was identified as one of the most active constituents in sappan wood. 7 In recent studies, the anti-inflammatory effects of brazilin in macrophages via novel mechanisms involving heme oxygenase-1 (HO-1) 8 and inducible nitric oxide synthase (iNOS) gene expression 9 were reported. The suppressive effect on iNOS gene expression by brazilin might provide a possible mechanism for its chemopreventive activity in cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…(Leguminosae) is distributed in Southeast Asia. It is used as an herbal medicine for the treatment of inflammation and to improve blood circulation (Nagai et al, 1984), influenza, allergic, and neuroprotective activities (Liu et al, 2009;Shen et al, 2007;Yodsaoue et al, 2009). This plant was used in Vietnamese traditional medicine for the treatment of menstrual and post-partum hematometra, trauma blood static, dizziness, post-partum blood losses, bloody dysentery, enteralgia, intestinal hemorrhage, infectious diarrhea, and for washing wounds (Bich, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the anti-influenza viral activity, 3) the anti-allergic activity, 4) and the neuroprotective activity 5) of Sappan Lignum or brazilin, the major constituent of Sappan Lignum, were reported. Although other compounds, including sappanchalcone and protosappanins A-E, are present in Sappan Lignum, there are few reports of their pharmacological activities.…”
mentioning
confidence: 99%